Novels of Everyday Life : the Series in English Fiction, 1850-1930. - Langbauer, Laurie (Cornell University Press, 2019)
Laurie Langbauer argues that our worldview is shaped not just by great public events but also by the most overlooked and familiar aspects of common life-"the everyday." This sphere of the everyday has always been a crucial component of the novel, but has been ignored by many writers and critics and long associated with the writing of women. Focusing on the linked series of novels characteristic of later Victorian and early modern fiction-such as Margaret Oliphant's Carlingford Chronicles or the Sherlock Holmes stories-she investigates how authors make use of the everyday as a foundation to support their versions of realism. What happens when-in the series novel, or in contemporary theory-the everyday becomes a site of contestation and debate? Langbauer pursues this question through the novels of Margaret Oliphant, Charlotte Yonge, Anthony Trollope, and Arthur Conan Doyle-and in the writings of Dorothy Richardson, Virginia Woolf, and John Galsworthy as they reflect on their Victorian predecessors. She also explores accounts of the everyday in the works of such theorists as Henri Lefebvre, Michel de Certeau, and Sigmund Freud, as well as materialist critics, including George Lukacs, Max Horkheimer, and Theodor Adorno. Her work shows how these writers link the series and the everyday in ways that reveal different approaches to comprehending the obscurity that makes up daily life.